Factors Influencing Households’ Willingness To Adopt Rooftop Solar Power In The Philippines - Palanca-Tan, Rosalina (Archīum Ateneo, 2024)
The Philippines is endowed with vast solar potential. Through rooftop solar power (RTSP), households directly participate in the clean energy transition, expanding renewable energy supply to meet increasing energy demand and effectively lowering electricity costs for themselves. Yet, RTSP in the country remains largely untapped. Using the Contingent Valuation framework, this study conducted a survey of households in Metro Manila and its neighboring provinces to identify the factors that influence adoption and willingness to pay for RTSP. Survey results reveal that both economic (mainly electricity bill reduction) and environmental benefits are well-recognized and positively correlated with RTSP adoption. The study found considerable RTSP adoption potential (82%) if both probable and definite intentions are considered. However, when only definite intentions are considered, adoption rate dropped to 20%. The returns to RTSP investments should increase for more households to seriously consider adoption. This necessitates greater government mediation and incentives such as a higher price for excess solar electricity in the net metering program.